Pengaruh Pajak, Tunneling Incentive, Dan Bonus Plan Terhadap Keputusan Perusahaan Untuk Melakukan Transfer Pricing - Lannai, Darwis (Jurnal Online Manajemen ELPEI, 2024)
This research took place at IDX (Indonesia Stock Exchange). The sample selection method in the study was a purporsive sampling method with a total sample of 15 companies. While the technique of collecting data collects data on company financial statements during the study period. Data analysis method used logistic regression with the help of SPSS software for windows 25.00. The results of the study prove Tax on the decision to conduct transfer pricing. The results of this study are supported by previous research conducted by Hartati, et al. (2014), and Oktavia, et al. (2012). Tunneling incentives do not affect transfer pricing decisions. The results of this study contradict the hypothesis research, but this study is supported by previous research conducted by Koestaman and Diyanty (2013), and the bonus plan is not related to the decision to conduct transfer pricing. The results of the study are contrary to hypothesis research, a study supported by previous research conducted by Jayengsari and Soetedjo (2013) and Aryanto, et al. (2013).